Evaluate Environmental Education of Designer: Environmental Responsible Behavior based on Literacy about Zero Waste - Rahmawaty, Dewi; ., Nadiroh; Husen, Achmad; Purwanto, Agung (International Journal of Membrane Science and Technology, 2023)
Zero waste is a concept in which the production of an environmentally friendly industry produces zero percent waste. Zero waste among designers is an important thing because it will have an impact on reducing the amount of waste. Environmental education in this case plays a role in providing education for designers so they can reduce waste. The role of environmental education can form Environmental Literacy (EL) and Environmental Responsible Behavior (ERB). The purpose of this study is to evaluate environmental education regarding the relationship between environmental literacy, attitudes towards zero waste, and designer personality with environmentally responsible behavior. The method used in this research is to use a descriptive method with data collection techniques using surveys. The results of this study show that the t-test for t-count > t-table (0.05; 148) 1.790 > 1.65 means that the correlation coefficient between environmental literacy, attitude towards Zero Waste, and personality environmentally responsible behavior is significant. Environmental education in this case plays an important role in increasing environmental literacy so it needs to be strengthened in schools. This study concludes that there is a relationship between various variables. The limitations of this study are the difficulty in obtaining a wider sample and only limited to designers.